Analisis Unsur Intrinsik Puisi dalam Kumpulan Puisi “Asmaraloka” Karya Usman Arrumy dan Rekomendasinya sebagai Bahan Ajar Apresiasi Puisi Tingkat SMA - Alpian, Rio; Suntoko, Suntoko; Seli Mauludani (GERAM (Gerakan Aktif Menulis), 2026)
Poetry appreciation learning in high schools requires teaching materials that are aesthetic, easy to read, and relevant to students' experiences. However, poetry materials used in class often do not fully consider readability, thematic proximity, and the text's potential as a means of poetry appreciation. This study aims to analyze the intrinsic elements of poetry in Usman Arrumy's Asmaraloka poetry collection, which is relevant as open material for high school poetry appreciation. The study used a qualitative descriptive method with a content analysis design with a structural approach. Data collection techniques were through bibliography, reading, and recording. The research data consisted of 20 selected poems from 52 poems in Asmaraloka, selected based on theme variation, representation of physical and spiritual elements, and pedagogical relevance. Physical elements are divided into diction, imagery, concrete words, figurative language, verification, and typography, while spiritual elements consist of theme, feeling, tone, and message. The findings of the analysis show that free rhyme is very dominant and confirms that the poet prioritizes the meaning of poetry when compared to aesthetic functions. Metaphor is the most frequently found figurative language by comparing one object with another. In addition, conventional typography dominates all poems, this shows the poet's consistency in creating poetry. The results of expert validation obtained an average of 3.8 with a category suitable for use. These findings indicate that Asmaraloka is relevant as an alternative teaching material for high school poetry appreciation.